Telecommunications as a means to access health information: an exploratory study of migrants in Australia - Louise Greenstock; Robyn Woodward-Kron; Catriona Fraser; Amie Bingham; Lucio Naccarella; Kristine Elliott; Michal Morris (SAGE Publishing, 2012)
Background. Health policies increasingly promote e-health developments (e.g., consumers' access to online health information) to engage patients in the health care. In order to make these developments available for culturally and socially diverse communities, not only do Internet accessibility, literacy and e-health literacy need to be taken into account, but consumers' preferences and information seeking behaviours for accessing health information have also to be understood. These considerations are crucial when designing major new health policy directions, especially for migration destination countries with culturally diverse populations, such as Australia. The aim of this study was to examine how people from a culturally and linguistically diverse (CALD) community use telecommunications (phone, mobile, Internet) to access health information. Design and Methods. A case study was conducted using a questionnaire exploring the use of telecommunications to access health information among CALD people. The study was carried out at a community health centre in a socially and economically disadvantaged area of Melbourne, a city of 4 million people with a large CALD and migrant population. Questionnaires were translated into three languages and interpreters were provided. Fifty-nine questionnaires were completed by users of the community health centre. Results. Most of the CALD participants did not have access to the Internet at home and very few reported using telecommunications to access health information. Conclusions. The findings of the study suggest that telecommunications are not necessarily perceived to be an important channel for accessing health information by members of the CALD community.